2016
DOI: 10.2967/jnumed.115.168344
|View full text |Cite
|
Sign up to set email alerts
|

Early Prediction of Tumor Response to Treatment: Preclinical Validation of 99mTc-Duramycin

Abstract: Noninvasive imaging of cell death can provide an early indication of the efficacy of tumor treatment, aiding clinicians in distinguishing responding patients from nonresponding patients early on. 99m Tcduramycin is a SPECT tracer for cell death imaging. In this study, our aim was to validate the use of 99m Tc-duramycin for imaging the early response of tumors to treatment. Methods: An in vitro binding assay was performed on COLO205 cells treated with 5-fluorouracil (3.1, 31, or 310 μM) and oxaliplatin (0.7 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 22 publications
(35 reference statements)
2
23
0
1
Order By: Relevance
“…Labeling with both SPECT ( 99m Tc) and PET ( 18 F, 68 Ga) radioisotopes and successful imaging of treatment-induced cell death in human lymphoma and lung and breast cancer (21) have been reported. Previously, our group has demonstrated the potential of 99m Tcduramycin to visualize radiotherapy- (15) and chemotherapyinduced (14,15) apoptosis. The sensitivity for apoptosis imaging was demonstrated by a 3-fold increase in 99m Tc-duramycin uptake (2 %ID/g) in colorectal cancer xenografts treated with irinotecan in combination with oxaliplatin versus vehicle-treated tumors, in good correlation with the tumor apoptotic response (4-to 7-fold increase).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Labeling with both SPECT ( 99m Tc) and PET ( 18 F, 68 Ga) radioisotopes and successful imaging of treatment-induced cell death in human lymphoma and lung and breast cancer (21) have been reported. Previously, our group has demonstrated the potential of 99m Tcduramycin to visualize radiotherapy- (15) and chemotherapyinduced (14,15) apoptosis. The sensitivity for apoptosis imaging was demonstrated by a 3-fold increase in 99m Tc-duramycin uptake (2 %ID/g) in colorectal cancer xenografts treated with irinotecan in combination with oxaliplatin versus vehicle-treated tumors, in good correlation with the tumor apoptotic response (4-to 7-fold increase).…”
Section: Discussionmentioning
confidence: 99%
“…After intravenous injection, 99m Tc-duramycin had favorable biodistribution, clearance, and pharmacokinetic profiles. Previously, we and others showed that 99m Tc-duramycin quickly cleared from circulation via the renal system, with low hepatic and gastrointestinal uptake (13)(14)(15). Radiotracer uptake in blood, muscle, liver, spleen, and kidneys was not significantly changed by conatumumab treatment (P .…”
Section: Ex Vivo Validationmentioning
confidence: 93%
See 1 more Smart Citation
“…Because of the known limitations associated with avidin-biotin systems (background) and green fluorescent protein (poor light penetration through tissues), 99m Tc is one of the most widely used radiolabels for duramycin. As such, 99m Tc-duramycin has been applied extensively to detect dead or dying cells in vivo, for example, in atherosclerotic plaques (23), in tumors challenged by different chemotherapy or radiotherapy schemes (24,25), or in different stages of lung injury (26), where it can be useful in the characterization of new cell death biomarkers.…”
mentioning
confidence: 99%
“…On the premise that PE and phosphatidylserine are regulated by the same mechanisms and that both are exposed during apoptosis [21] and after irradiation [1] a number of studies investigated whether PE exposure was upregulated after chemotherapy. It was demonstrated that externalisation of PE, detected by duramycin, could potentially be a marker of early apoptosis and could be utilised as a detection method for the response to chemotherapy treatment [22][23][24].…”
Section: Introductionmentioning
confidence: 99%